Nanotechnology cookbook : practical, reliable and jargon-free experimental procedures - Collins, Andrew (Elsevier Science, 2012)
The peculiarities of materials at the nanoscale demand an interdisciplinary approach which can be difficult for students and researchers who are trained predominantly in a single field. A chemist might not have experience at working with cell cultures or a physicist may have no idea how to make the gold colloid they need for calibrating an atomic force microscope. The interdisciplinary approach of the book will help you toquickly synthesize information from multiple perspectives. Nanoscience research is also characterized by rapid movement within disciplines. The amount of time it take.